Psychometric evaluation of the newcastle satisfaction with nursing scales - Piredda, M.; Vellone, E.; Piras, G.; Fida, R.; Latour, Jos; Matarese, M.; Alvaro, R.; De Marinis, M. (Lippincott Williams and Wilkins, 2015)
This study tested the psychometric properties of the Italian version of the Newcastle Satisfaction with Nursing Scales through factor analysis with 659 medical and surgical inpatients. One factor was found for the Scale Satisfaction and 4 factors for the Scale Experiences: Carelessness, Emotional support, Relationship/information, and Caring times. This validation makes available to nurses and managers a multidimensional tool able to discriminate between different care experiences and to identify areas for care improvement.